(untitled) (Communications in Computational Physics, 2018)
Direct numerical simulation of vertical rotating open-channel flow with heat transfer has been carried out for the rotation number Nτ from 0 to 0.1, the Prandtl number 1, and the Reynolds number 180 based on the friction velocity of non-rotating flow and the height of the channel. The ob jective of this study is to reveal the effect of rotation on the characteristics of turbulent flow and heat transfer, in particular near the free surface and the wall of the open-channel. Statistical quantities, e.g., the mean velocity, temperature and their fluctuations, turbulent heat fluxes, and turbulence structures, are analyzed. The depth of surface-influenced layer decreases with the increase of the rotation rate. In the free surface-influenced layer, the turbulence and thermal statistics are suppressed due to the effect of rotation. In the wall-influenced region, two typical rotation regimes are identified. In the weak rotation regime with 0 < Nτ < 0.06 approximately, the turbulence and thermal statistics correlated with the spanwise velocity fluctuation are enhanced since the shear rate of spanwise mean flow induced by Coriolis force increases; however, the other statistics are suppressed. In the strong rotation regime with Nτ > 0.06, the turbulence and thermal statistics are suppressed significantly because the Coriolis force effect plays a dominant role in the rotating flow. To elucidate the effect of rotation on turbulent flow and heat transfer, the budget terms in the transport equations of Reynolds stresses and turbulent heat fluxes are investigated. Remarkable change of the direction of streak structures based on the velocity and temperature fluctuations is discussed.